Production of extracellular emulsifying agent by Streptomyces SP. MC1 - Pereira, Claudia Elizabeth (2011)
Emulsifier of microbial origin have significant implications in the biological treatment of pollutants from environmental. They are employed in mechanisms for hydrocarbon and inorganic pollutants bioremediation, including heavy metals. Streptomyces sp. MC1 isolated from sugar cane, showed significant capacity to reduction of Cr(VI) to Cr(III) in minimal medium supplemented with sulphate or phosphate ions. The aim of this work is to evaluate now the effect of these ions, either in presence and absence of Cr(VI) on emulsifier production from this strain. Cells of Streptomyces sp. MC1 were grown in liquid minimal medium either with or without 20 mg/L of Cr(VI) added as K2Cr2O7 , and different concentrations of Na2SO4 (5 to 20 mM). Cultures were incubated at 30ºC in orbital shaker at 170 rpm. Emulsiﬁers production was monitored using kerosene as water-immiscible substrate. After 48 h of cultivation, only in presence of phosphate ions it was detected the emulsiﬁer production in supernatant of this strain, with a highly-stable emulsion. However, supplementation of Cr(VI) to the minimal medium inhibited the emulsifier production. Results presented here may have important implications in bioremediation of hydrocarbon and inorganic pollutants. Therefore, optimization studies of produced emulsifier could be required for future applications.